A LITERARY CRITICAL DISCOURSE ON QURANIC HISTORY IN SEVENTH-CENTURY ARABIA - Elimam, Ahmed Saleh; Husain, Mohammad Khalid (Journal of Al-Tamaddun, 2018)
The Qur’an is the holy scripture of Islam. For Muslims, the Qur’an is the literal word of Allah revealed via the angel Gabriel to the last Prophet Muhammad who relayed the revelation, verbatim, to his followers. As one of the essential beliefs of Muslims, the Qur’an is inimitable in its composition and argue that, just as the earlier prophets of Allah were given the power to perform certain miracles to prove to their respective followers that they were genuine prophets, the Qur’an is the proof of Muhammad’s prophethood. Muslim scholars argue that the Arabs, whose literary tradition had reached its zenith just before the time of the revelation of the Qur’an, were fascinated by its style. Many of Prophet’s contemporaries acknowledged the Qur’an as a non-human or divine composition on hearing the recitation of some of its passages. This article sets out first of all to explore the Arabic literary tradition around the time of the revelation of the Qur’an, since it is against this background that their evaluation of the composition of the Qur’an may be understood and, secondly, to examine the relevant Islamic literature on the response of the Arabs to the Qur’an and finally shed some light on the inimitable style of the Qur’an.